PARADIPLOMACY TOWARDS THE WORLD FASHION CITY: STUDY ON JEMBER DISTRICT - Dermawan, Windy; Rahminita, Siti Hediati; Affandi, RMT Nurhasan; Azmi, Fuad (Faculty of Social and Political Sciences University of Bangka Belitung, 2025)
This study examines the role of the Jember Fashion Carnaval (JFC) as a paradiplomatic tool for the Jember district government in its efforts to establish itself as a world fashion city. Using a qualitative approach, the research analyzes how JFC functions as a cultural, economic, and political instrument in international relations, drawing on theoretical frameworks from Aldecoa & Keating, Lecours, Dávila & Silva, and Prieto. Data was collected through in-depth interviews with key stakeholders (organizers, government officials, and international participants), media analysis, and documentation studies, with thematic analysis applied to identify patterns in JFC’s diplomatic impact. The findings reveal that JFC has successfully enhanced Jember’s global visibility, facilitated cross-cultural exchanges, and contributed to local economic growth through tourism and foreign investment interest. However, challenges such as inadequate legal frameworks, limited funding, and a lack of specialized human resources hinder the institutionalization of paradiplomacy in Jember. Despite these constraints, JFC demonstrates the potential of subnational cultural diplomacy in projecting local identity and supporting national soft power. The study concludes with policy recommendations, including strengthening institutional support, diversifying funding mechanisms, and integrating JFC into long-term regional development strategies. By addressing these gaps, Jember can maximize JFC’s role in achieving its aspirations as a world fashion city while contributing to broader discussions on paradiplomacy and cultural diplomacy in international relations